Peran Dukungan Sosial Terhadap Resiliensi Pasien Tuberkulosis Dalam Mendukung Keberhasilan Terapi Obat Anti Tuberkulosis: Implikasi Bagi Pelayanan Kefarmasian - St. Rahmatullah; Yulian Wahyu Permadi; Irnawati Irnawati; Riska Kurnia Oktaviani; Aniq Nanda (Lembaga Bale Literasi, 2026)
Psychosocial factors supporting patient treatment adherence significantly determine the success rate of tuberculosis (TB) management, in addition to the utilization of effective Anti-Tuberculosis Drugs (ATDs). In this context, self-resilience and social support are identified as two pivotal determinants. This study aimed to map the correlation between social support and resilience among TB patients, while exploring its implications for the optimization of pharmaceutical care. Utilizing an analytical survey with a cross-sectional study design, this research involved 51 patient families within the working area of the Doro I Public Health Center in Pekalongan Regency, recruited via a total sampling technique. Quantitative data were collected using the Multidimensional Scale of Perceived Social Support (MSPSS) and the Connor-Davidson Resilience Scale (CD-RISC), followed by analysis using the Chi-square test. Statistical analysis confirmed a significant relationship between social support and patient resilience (p = 0.004). This finding indicates that enhancing social support can strengthen patient resilience, which in turn promotes the effectiveness of ATD therapy. Consequently, the integration of counseling, education, and family empowerment in treatment supervision is essential to be adopted into standard pharmaceutical care.